New Language Leader. Elementary: Coursebook with MyEnglishLab - Lebeau I. Ian (Always learning)
New Language Leader takes an intelligent approach to building the confidence and skills students need to succeed in academic study and use English in a globalised world. Meet the Expert authentic video interviews with leading professionals and academics bring topics to life and stretch students' ability to understand real English; Study Skills videos develop communication and collaboration skills, setting students up for future success; Contemporary topics and issues stimulate students' minds and develop critical thinking skills.